2011
DOI: 10.1007/s12350-011-9338-3
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of F-18 FDG and ultrasound analysis of carotid plaque

Abstract: Our results show that F-18 FDG carotid PET/CT can depict metabolically active atherosclerotic plaques, and suggest that F-18 FDG carotid PET/CT can be used as a noninvasive imaging modality for functional evaluation of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Although 18 F-FDG uptake and circulating hsCRP are both markers of inflammation, there is no clear consensus regarding their relation in atherosclerosis patients (19)(20)(21). Given the widely recognized role of hsCRP in predicting cardiovascular events, lack of correlation with 18 F-FDG uptake suggests that the 2 markers may represent different aspects of atherosclerotic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 18 F-FDG uptake and circulating hsCRP are both markers of inflammation, there is no clear consensus regarding their relation in atherosclerosis patients (19)(20)(21). Given the widely recognized role of hsCRP in predicting cardiovascular events, lack of correlation with 18 F-FDG uptake suggests that the 2 markers may represent different aspects of atherosclerotic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there have been only a few studies with relatively small numbers of subjects that compared circulating hsCRP and 18 F-FDG uptake, and the findings have shown mixed results (19)(20)(21). In this study, we thus evaluated a large cohort of asymptomatic adults to investigate the relation of carotid artery 18 F-FDG uptake, hsCRP concentration, and estimated risk based on general cardiovascular Framingham risk scores (FRSs).…”
mentioning
confidence: 99%
“…Arterial uptake in one vascular region correlates strongly with its anatomical pair, and more strongly with neighbouring regions than more distally. Plaques with high-risk features on MRI (large lipid core [49] or intraplaque haemorrhage [63]) or ultrasound [64,65] (echolucency) have higher FDG than more stable phenotypes. Aortic uptake has been shown to correlate with circulating biomarkers matrix metalloproteases 1, 3 and 9 [54,66], and an inverse correlation has been reported with the atheroprotective biomarkers adiponectin and plasminogen activator inhibitor 1 [54,66].…”
mentioning
confidence: 99%
“…32,33 Furthermore, TBR calculated as arterial standardized uptake value (SUV) score divided by venous blood SUV is generally used as an index of a quantitative parameter of vascular inflammation. 23,[32][33][34][35][36] Indeed, Tawakol et al 23 reported that TBR values in the carotid arteries were closely correlated with accumulation of CD68-positive macrophages in the corresponding histological sections of patients with severe carotid stenoses (r=0.85; P<0.001). Carotid TBR values were higher in patients with high-risk morphological features of atherosclerotic plaques, such as echolucent plaques, positive remodeling, luminal irregularity, and low attenuation in computed tomographic, than those without.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Carotid TBR values were higher in patients with high-risk morphological features of atherosclerotic plaques, such as echolucent plaques, positive remodeling, luminal irregularity, and low attenuation in computed tomographic, than those without. 34,35 In addition, carotid artery TBR has been shown to strongly predict subsequent cardiovascular disease in patients with no previous history of cardiovascular disease independent of traditional risk factors. 36 Moreover, when we examined which variables including carotid artery SUV, venous blood SUV, and TBR value were independently associated with %FMD, TBR value was the strongest correlate of decreased %FMD (β=−2.506; P=0.002).…”
Section: Methodological Considerationsmentioning
confidence: 99%